2009
DOI: 10.1073/pnas.0908816106
|View full text |Cite
|
Sign up to set email alerts
|

Large-scale patterns in biodiversity of microbial eukaryotes from the abyssal sea floor

Abstract: Eukaryotic microbial life at abyssal depths remains "uncharted territory" in eukaryotic microbiology. No phylogenetic surveys have focused on the largest benthic environment on this planet, the abyssal plains. Moreover, knowledge of the spatial patterns of deep-sea community structure is scanty, and what little is known originates primarily from morphology-based studies of foraminiferans. Here we report on the great phylogenetic diversity of microbial eukaryotic communities of all 3 abyssal plains of the south… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
125
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 102 publications
(132 citation statements)
references
References 54 publications
(52 reference statements)
7
125
0
Order By: Relevance
“…Our results from the SouthEast Atlantic, thus, corroborate the report of Scheckenbach et al (2010) and are also in agreement with a comparable study of communities of prokaryotes from the same sampling regions also reporting of statistically indistinguishable communities from both the Angola and the Guinea Basin, as well as the Guinea Basin and the Namibia Abyssal Plain (Schauer et al, 2009). Furthermore, as the kinetoplastid-specific clone libraries from the South-East Atlantic, reported here, show the same pattern as clone libraries built with general eukaryotic primers as reported by Scheckenbach et al (2010), it is admissible to assume that the pattern reported here for both the South-East and South-West Atlantic may be similar for other groups of microbial eukaryotes. The assumption of McClain and Hardy (2010), that geographical ranges may increase with depth as environmental conditions become more constant and homogeneous, may therefore be plausible.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Our results from the SouthEast Atlantic, thus, corroborate the report of Scheckenbach et al (2010) and are also in agreement with a comparable study of communities of prokaryotes from the same sampling regions also reporting of statistically indistinguishable communities from both the Angola and the Guinea Basin, as well as the Guinea Basin and the Namibia Abyssal Plain (Schauer et al, 2009). Furthermore, as the kinetoplastid-specific clone libraries from the South-East Atlantic, reported here, show the same pattern as clone libraries built with general eukaryotic primers as reported by Scheckenbach et al (2010), it is admissible to assume that the pattern reported here for both the South-East and South-West Atlantic may be similar for other groups of microbial eukaryotes. The assumption of McClain and Hardy (2010), that geographical ranges may increase with depth as environmental conditions become more constant and homogeneous, may therefore be plausible.…”
Section: Discussionsupporting
confidence: 92%
“…This may underline the constant and homogeneous conditions prevailing over large spatial distances at abyssal depths. Two previous studies already reported of similar, and even statistically not distinguishable, communities of microbial eukaryotes at larger scales from the abyssal North-West Atlantic (Countway et al, 2007) and the abyssal South-East Atlantic (Scheckenbach et al, 2010). The latter study equally reported of statistically not distinguishable communities from the Angola and the Guinea Basin, and also of statistically distinct communities from the Namibia Abyssal Plain.…”
Section: Discussionmentioning
confidence: 56%
See 2 more Smart Citations
“…So far, studies utilising these techniques are providing increasing evidence that many microbial communities are not homogenised through space, but display significant structure just like many plant and animal communities do (Martiny et al, 2006;Hanson et al, 2012;Nemergut et al, 2013). These findings have principally been based on studies examining bacteria (Fierer and Jackson, 2006;Bryant et al, 2008;Fulthorpe et al, 2008;Lauber et al, 2009;Knief et al, 2010;Ghiglione et al, 2012); the relatively fewer studies examining eukaryotic microbes also show differential patterns of community composition in space (Dumbrell et al, 2010;Scheckenbach et al, 2010;Bokulich et al, 2014;Taylor et al, 2014).…”
Section: Introductionmentioning
confidence: 99%